A Review on Water Quality Models: QUAL, WASP, BASINS, SWAT and AGNPS - Mulla, Najmussahar H; Krishna, Dr. B. M.; Kumar, Dr. B. Manoj (International Journal of Scientific Research in Civil Engineering, 2019)
Water is essential for life, human civilization, and to protect the nature and its resources. Any natural body of water may be viewed as a system composed of a number of complex interacting subsystems each having its own unique characteristics. The current population growth rate, human lifestyle significantly influences the physical, chemical and biological characteristics of water making it scarce. Scientific water resources management is the need of the day. The evaluation and analysis of point and non-point water pollution loads is a very important issue to be addressed presently. Models can be effective tools in assisting efficient ways for water resources development, treatment and use. Each water quality model has its own unique purpose and simulation characteristics and hence has to be reviewed thoroughly before use. The main goal of this paper is to address the recent developments in five well known water quality models: QUAL, WASP, BASINS, SWAT and AGNPS. The current focus is on improving the knowledge in the field of modeling for devising the new generation of models. All concerned water sector parties must make model usage compulsory for good governance and sustainable water resources management. The challenges of this path are inclusiveness, transparency, efficiency and productivity. Geospatial technologies have proven to be an effective enabler to meet these challenges. Integration of models with one another and Geographic Information System (GIS) and Remote Sensing (RS) is important to solve data related and simulation related problems.
Keywords: Nonpoint pollution; Water quality models; QUAL; WASP; BASINS; SWAT; AGNPS